1997
DOI: 10.1038/bjc.1997.331
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative reverse transcriptase polymerase chain reaction-based assay to detect carcinoma cells in peripheral blood

Abstract: Summary The presence of tumour cells in the circulation may predict disease recurrence and metastasis. To improve on existing methods of cytological or immunocytological detection, we have developed a sensitive and quantitative technique for the detection of carcinoma cells in blood, using the reverse transcriptase polymerase chain reaction (RT-PCR) identifying transcripts of the pancarcinoma-associated tumour marker EGP-2 (KSA or 17-lA antigen). The amount of EGP2 mRNA was quantified using an internal recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…1 in 100,000 cells, [12]). Most studies, in agreement with the present authors9 data, excluded the illegitimate expression of cytokeratin 20, CEA and EPG2 by normal blood cells [7,9,11,17,21], although a highly sensitive nested PCR revealed CEA expression by normal blood cells in a low percentage of normal subjects due to illegitimate transcription or to false positives [10,12], and 20% of lung adenocarcinoma can aberrantly express CK20 [15]. Therefore, before the analysis to detect circulating micrometastases, the current authors recommend that a number of blood samples from normal subjects be tested with the RT-PCR procedure used in order to exclude illegitimate transcription.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…1 in 100,000 cells, [12]). Most studies, in agreement with the present authors9 data, excluded the illegitimate expression of cytokeratin 20, CEA and EPG2 by normal blood cells [7,9,11,17,21], although a highly sensitive nested PCR revealed CEA expression by normal blood cells in a low percentage of normal subjects due to illegitimate transcription or to false positives [10,12], and 20% of lung adenocarcinoma can aberrantly express CK20 [15]. Therefore, before the analysis to detect circulating micrometastases, the current authors recommend that a number of blood samples from normal subjects be tested with the RT-PCR procedure used in order to exclude illegitimate transcription.…”
Section: Discussionsupporting
confidence: 77%
“…Cytokeratin 19, cytokeratin 20 and EPG2 mRNA were analysed as follows: RT: 25uC for 10 min; 42uC for 30 min; 95uC for 5 min; polymerase chain reaction (PCR): 94uC for 5 min, followed by 30 cycles (95uC for 30 s, 55uC for 30 s, 72uC for 30 s) and 72uC for 5 min, using the previously described primers cytokeratin 19 [14], cytokeratin 20 [21] and EPG2 [17]. These primers were designed to exclude amplification of known pseudogenes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At high RNA concentrations (1 µg), both carcinoma and lymphoblastoid lines expressed EGP-2 RNA; however, at lower concentrations (10 ng) expression was absent in lymphoblastoid lines. More recently, without immunobead selection, in terms of EGP-2 expression, it has been also demonstrated that bone marrow aspirates (Helfrich et al, 1997) or peripheral blood cells (de Graaf et al, 1997) could yield false-positive reactions by sensitive RT-PCR methods even with samples obtained from normal volunteers. By flow cytometric examination, 83% of epithelial cell lines expressed EGP-2 cell-surface protein, usually at relatively high levels, whereas B-lymphoblastoid lines were uniformly negative.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the immunocytochemistry method needs to be further developed before it can be used routinely in the clinic and it is not clear whether the most frequently employed reverse transcription PCR (RT-PCR) assays for cytokeratin 18 or 19 or pancarcinoma-associated tumour marker (KSA or 17-1A antigen) have the specificity to be reliably used (Kvalheim, 1996;Helfrich et al, 1997).…”
Section: Discussionmentioning
confidence: 99%